Corel WordPerfect 7.0 for Windows 95 with Disk - Catherine Skintik (Prentice Hall, 1998)
An excellent way to learn Corel WordPerfect 7.0 for Windows 95 in a short period of time. This text covers the most commonly used features of the software application in 12-15 hours. Numerous screen captures and hands-on activities are integrated throughout the text to provide reinforcement. Each lesson begins with a list of objectives and an introduction. Also listed at the beginning of each lesson is the estimated completion time